Reduction of Garbage in the Diet of Nonbreeding Glaucous Gulls Corresponding to a Change in Waste Management - Weiser, Emily L.; Powell, Abby N. (ARCTIC, 2011)
Glaucous gulls (Larus hyperboreus) are major predators in the Arctic and may benefit from human development. We studied use of garbage by glaucous gulls in Barrow, Alaska, in 2007, when municipal waste was disposed of in a landfill, and in 2008, when it was incinerated. In both years, diet samples from breeding adult gulls contained less garbage than those from loafing nonbreeding gulls (mostly subadults of less than four years), possibly because the breeding colony was more distant than many loafing sites from the landfills. Although breeding gull samples showed no change, garbage in regurgitated pellets and food remains of nonbreeding gulls was significantly less prevalent in 2008 than in 2007 (28% vs. 43% occurrence in diet samples), and this reduction could be explained by the switch from landfill to waste incineration. Yet garbage remained a substantial part of nonbreeding gull diet after the management change. Other aspects of waste management, such as storage prior to disposal, may also be important in limiting scavengers’ access to garbage and thus reducing the indirect impact of human development on prey species of conservation concern. Dans l’Arctique, le goéland bourgmestre (Larus hyperboreus) est un important prédateur, et celui-ci pourrait bénéficier du développement humain. Nous nous sommes penchés sur l’utilisation qu’a fait le goéland bourgmestre des déchets à Barrow, en Alaska, en 2007 lorsque les déchets municipaux aboutissaient dans un site d’enfouissement puis en 2008, lorsque les déchets municipaux étaient incinérés. Au cours de ces deux années, les échantillons alimentaires prélevés chez les goélands adultes reproducteurs renfermaient moins de déchets que les échantillons prélevés auprès des goélands non-reproducteurs qui flânaient (des goélands immatures de moins de quatre ans dans la plupart des cas), probablement parce que la colonie de reproduction était plus loin des sites d’enfouissement que des nombreux lieux de flânerie. Bien que les échantillons prélevés chez les goélands ...